A freshwater biodiversity hotspot under pressure – assessing threats and identifying conservation needs for ancient Lake Ohrid - G. Kostoski; C. Albrecht; S. Trajanovski; T. Wilke (Biogeosciences, 2010)
Immediate conservation measures for world-wide freshwater resources are of eminent importance. This is particularly true for so-called ancient lakes. While these lakes are famous for being evolutionary theatres, often displaying an extraordinarily high degree of biodiversity and endemism, in many cases these biota are also experiencing extreme anthropogenic impact. Lake Ohrid, a major European biodiversity hotspot situated in a trans-frontier setting on the Balkans, is a prime example for a lake with a magnitude of narrow range endemic taxa that are under increasing anthropogenic pressure. Unfortunately, evidence for a "creeping biodiversity crisis" has accumulated over the last decades, and major socio-political changes have gone along with human-mediated environmental changes. Based on field surveys, monitoring data, published records, and expert interviews, we aimed to (1) assess threats to Lake Ohrids' (endemic) biodiversity, (2) summarize existing conservation activities and strategies, and (3) outline future conservation needs for Lake Ohrid. We compiled threats to both specific taxa (and in cases to particular species) as well as to the lake ecosystems itself. Major conservation concerns identified for Lake Ohrid are: (1) watershed impacts, (2) agriculture and forestry, (3) tourism and population growth, (4) non-indigenous species, (5) habitat alteration or loss, (6) unsustainable exploitation of fisheries, and (7) global climate change. Among the major (well-known) threats with high impact are nutrient input (particularly of phosphorus), habitat conversion and silt load. Other threats are potentially of high impact but less well known. Such threats include pollution with hazardous substances (from sources such as mines, former industries, agriculture) or climate change. We review and discuss institutional responsibilities, environmental monitoring and ecosystem management, existing parks and reserves, biodiversity and species measures, international conservation activities, and ongoing research on conservation and raising of public awareness. Following this summary, we evaluate the status quo and future of Lake Ohrid and its biota. A comprehensive conservation strategy should include measures that result in an immediate reduction of nutrient input, particularly with phosphorus, in order to slow down the ongoing eutrophication process. The existing watershed management should become more effective. Implementation and particularly with a view to the enforcement of national laws should be enhanced. Increased research on the lakes' limnology, biodiversity, and conservation management practices are necessary. The latter research should identify conservation priorities. Public awareness should be enhanced. Facing these parallel needs to protect the unique biodiversity of Lake Ohrid, we suggest urging (a) implementation and enforcement of the General Management Plan that would ensure long-term integrated and sustainable use of the lake and its watershed, (b) scientific studies on ecology, biodiversity and effects of human impact, (c) the establishment of Core Conservation areas (CCA), including underwater reserves, and (d) Coastal Zone Management (CZM) areas that would constitute buffer zones for the CCAs around the lake. Given the number of identified threats, it is clear that only concerted international action can stop or at least slow down further degradation of Lake Ohrid and the creeping biodiversity crisis already evident. All conservation activities should, among others, ultimately lead to a trans-boundary major conservation area of the Ohrid-Prespa region that would allow long-term integration of both humans and nature.